MODEL SIMULASI ALIRAN PERPIPAAN PADA INFRASTRUKTUR PEMBENIHAN UDANG (HACHERY) SISTEM MELALUI PENDEKATAN RECIRCULATING AQUACULTURE SYSTEM (RAS) - Hermansyah, Hadi; Azmanajaya, Emil; Yanti, Nur; Kurniawan, Yudi (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
The shrimp nursery infrastructure consists of nursery tanks, mechanical filters, biological filters, and ultraviolet (UV) filters. This study aimed to simulate the water level elevation (head) of shrimp nursery infrastructure, especially nursery tanks. The placement of the nursery greatly affects the elevation of the water table owing to the loss of energy (headloss) that occurs in the flow. The nursery tub used in this study was round and consisted of four tubs made of fiber resin measuring 250 cm in diameter and 120 cm in height. The bottom of the tub was placed at an elevation of +40 cm above the ground. The simulation was conducted for 24 hours. The results of the EPANET 2.2 simulation showed head fluctuations in each nursery with the highest elevation (1.38 m and the lowest (1.20 m, from the data. The head fluctuated constantly after 6 h of the flow. The optimal pipe diameters were 3